Comparative Analysis of Equestrian Facilities in the North Great Plain Region - Müller, Anetta; Bács, Zoltán; Bácsné Bába, Éva; Oláh, János; Pfau, Christa; Molnár, Anikó (International Journal of Engineering and Management Sciences, 2019)
Equestrian services appear in recreation, sports and tourism as well. The favorable natural and cultural values of Hungary and the image of the equestrian nation based on the traditions of the horse provide a favorable background for the development of supply elements. The lowland character and horse culture of the Northern Great Plain region, and the continuous development of horseback riding services here, reinforces the equestrian supply element in the field of sport and leisure. Our in - depth interviews were conducted among service providers with a “horseshoe rating” (N = 11) operating in the Northern Great Plain Region. The results show that all service providers consider and plan the development of equine, infrastructure and human resources, although the source of its financing is different (from state, other successful businesses, realized business results of equestrian enterprises). Equestrian service providers with no horseshoe rating have identified the improvement of quality, the 3, 4, and 5 horseshoe qualified service providers for the expansion of the complex program offering and product diversification.